USEFULNESS OF LEFT VENTRICLE DYSSYNCHRONY ASSESSMENT BEFORE CARDIAC RESYNCHRONIZATION IMPLANTATION - Lipoldova, Jolana; Ozabalova, Eva; Meluzin, Jaroslav; Novak, Miroslav; Vitovec, Jiri (Biomedical papers, 2010)
Background: A number of trials have demonstrated the effect of cardiac resynchronization therapy (CRT) on functional improvement and reversed left ventricle remodeling. Meeting contemporary guidelines approximately 30- 40% of patients do not respond to CRT (non-responders).Aim: To quantify the predictive ability of basal QRS width and basal echocardiographic parameters of left ventricle contraction dyssynchrony in our group of CRT patients. To compare effectiveness of these parameters assessment in patients with ischemic (iCMP) and non-ischemic cardiomyopathy (niCMP) and with sinus rhythm (SR) and atrial fibrillation (AF).Patients and methods: 194 patients after successful introduction of CRT device were evaluated. Evaluation of NYHA function class, QRS width and echocardiographic parameters including parameters of left ventricle contraction dyssynchrony (SPWMD: septal-to-posterior wall motion delay, Ts-sep-lat: time interval between maximum of systolic movement of septum and lateral wall using tissue Doppler imaging, IVMD: interventricular mechanical delay) performed before implantation and 3 months after implantation of CRT device.Results: Responder (improved in NYHA class after CRT) rate was 61%. SR patients showed higher benefit compared to AF patients (responder rate 63% vs. 52%, p
Keywords: Cardiac resynchronization therapy/Left ventricle dyssynchrony/Prediction of CRT response